The influence of the Regulation of the Minister of Health on food product groups designated for sale in educational establishments on the health behaviours of students - Bieniak, Monika; Chałdaś-Majdańska, Justyna; Rząca, Marcin Stanisław; Kocka, Katarzyna (Journal of Education, Health and Sport, 2017)
Introduction. Nutritional habits are among the elements of lifestyle which have an impact on health. Studies show that nutritional habits developed at a young age form a basis for future behaviour, so developing beneficial health behaviours by the youngest age groups is so crucial. Proper health behaviours have an impact on development and the state of health not only during childhood but also in the adult life, preventing negative effects on health. Objective. To identify the influence of the Regulation of the Minister of Health on food product groups designated for sale in educational establishments on the health behaviours of students. Material and methods. 477 lower-secondary and secondary school students from the Lubelskie and Mazowieckie provinces participated in the survey. The diagnostic survey method was used, together with the self-developed questionnaire technique. Results. Almost 1/3 of the students (32%) regularly bought at their school shop or a shop located near their school. 14% of the students were not aware that the regulation on the sales of food products in school shops was in force. After the regulation was passed the number of students buying sweet buns, sweets and salty snacks dropped; however, the problem has not been completely eliminated. The analysis of the self-designed study results demonstrates that the number of healthy products recommended for the age group increased only slightly. Nearly half of the students (49%) did not notice changes in the product range available in school shops. Only 26% were satisfied with the introduced changes. Conclusions. 1. Not all of the surveyed students are aware of the Regulation of the Minister of Health on food product groups designated for sale in educational establishments and the related product range changes. 2. The regulation has resulted in some changes in the everyday nutrition of lower-secondary and secondary schools. 3. The product range in school shops still contributes to improper nutritional habits among school students.